Implementation of the Adiwiyata Program at SMAN 1 Wonoayu: Study of the Role of Schools in Realizing Environmental Awareness - Mursyidah, Lailul; Ilmi Usrotin Choiriyah, Ilmi; Rodiyah, Isnaini (Indonesian Journal Publisher, 2024)
This research aims to analyze the implementation of the Adiwiyata program at SMAN 1 Wonoayu, Sidoarjo. The focus of this research is the factors that influence the effectiveness of its implementation. Using a descriptive qualitative approach. Apart from that, this research collected data through interviews with school principals, the Adiwiyata team, teachers and students, as well as field observations and documentation. Data analysis was carried out using the Miles & Huberman technique, including data reduction, data presentation, and drawing conclusions. The research results show that the Adiwiyata program at SMA Negeri 1 Wonoayu has been running well, but there are several problems that need to be overcome. Limited financial resources are the main obstacle in providing adequate facilities and infrastructure. Apart from that, the lack of socialization and direction regarding plant breeding techniques to the new Adiwiyata team also hindered the effectiveness of the program. The implication of this research is the need to increase budget allocations for the Adiwiyata program as well as strengthening socialization and technical training for the implementing team. In this way, it is hoped that the implementation of the Adiwiyata program can run more optimally and contribute to increasing awareness and participation of all school residents in environmental conservation.